The salinity anomalies due to nutrients and inorganic carbon in the Bohai Sea - Ji, Fengying; Yang, Jinkun; Ding, Feng; Zheng, Bing; Ning, Pengfei (Frontiers in Marine Science, 2024)
As a new seawater standard, the International Thermodynamic Equation of Seawater-2010 (TEOS-10) has made it possible to accurately calculate salinity changes caused by small changes in the relative proportions of inorganic dissolved constituents in the open ocean and thus to accurately calculate the thermodynamic properties of seawater. However, offshore and semi-enclosed seas are subject to the dual influence of geo-biochemical processes and terrestrial inputs, and the spatial and temporal variations in the relative composition of their seawater are more complex, resulting in very few studies of salinity change due to changes in the relative composition in these regions, and the applicability of the TEOS-10 in these seas needs to be further evaluated. The Bohai Sea is a typical semi-enclosed sea that has accumulated a large amount of physical oceanography and marine chemistry measurements, making it an ideal area to study the effects of changes in the relative composition of seawater on salinity. Based on repeated measurements of Section B in the Bohai Sea from 1985 to 2020, complemented by quasi-synchronous large-scale measurements of the Bohai Sea from 2006 to 2007, this study found that [HCO3−] and [Ca2+] ions anomalies dominate the relative composition anomalies of dissolved substances in this sea relative to the Standard Sea Water (SSW). These additional components could increase the absolute salinity SA by up to 0.1 g·kg-1 and the practical salinity SP by 0~0.04 according to the TEOS-10 algorithm and the mathematical model Pa08. Based on the specific environmental characteristics of the Bohai Sea, the sources, spatial and temporal variations, and influencing factors of the relative compositional anomalies are analyzed, and the empirical formulas of the absolute salinity anomaly δSA and practical salinity anomaly δSP for the Bohai Sea are further fitted, with the uncertainty of 0.007~0.021 g·kg-1 for δSA and 0.003~0.008 for δSP. The above results can not only improve the accuracy of the thermodynamic properties of the Bohai Seawater, but also provide the compatibility level of the long-term salinity changes in the Bohai Sea and its adjacent waters.